Monitorowanie dokonań ośrodków odpowiedzialności - Lew, Grzegorz (Performance Monitoring of Responsibility Centres, 2006)
The article presents some issues connected with monitoring of work in some responsibility centers within an enterprise. Well-organised monitoring of work in such centers is the basis for quality assessment of the places and is an important element of controllership system in the enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 227-232